Reflections of Prophetic Values on Strengthening Da'wah in the Digitalization Era - Suud Sarim Karimullah; Rahman Rahman; St. Rahmah; Fawwaz Elmurtadho (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Da'wah is an effort to spread religious teachings and strengthen the faith and practice of the people. Therefore, in da'wah, it is essential to reflect on prophetic values so that da'wah can be delivered correctly and by religious teachings. This study reflects on prophetic values to strengthen da'wah in the digitalisation era. This study is qualitative research in the form of library research with normative-philosophical research type with a conceptual research category that uses a descriptive-analytical research approach. Therefore, the results of the study state that strengthening da'wah in the digitalisation era can take advantage of technology to expand its reach and increase its effectiveness of da'wah. However, in using technology, it is also necessary to reflect prophetic values to avoid deviating from religious teachings. The existence of prophetic values such as humanisation, liberation and transcendence that are integrated to ground Islamic values in the lives of Muslims can be the basis for realising da'wah activities that uphold the values of benefit for human social life. Therefore, Islamic da'wah activities are projected to instil Islamic da'wah values that can synergistically empower human and natural resources because it not only aims to strengthen the vertical dimension of tawhid but also includes horizontal relationships with fellow humans and all creatures.